From the history of the development of tobacco farming as the most important branch of commercial agriculture in the provinces of the South Caucasus in the second half of the XIX – early XX centuries - Almaz M. Ismailova (Кавказология)
The article focuses on the evolution of tobacco cultivation in the South Caucasus over the research period. The author investigates the spread of this technological culture throughout all provinces in the specified region. Information is provided on the quantity of land occupied for tobacco cultivation, tobacco types, industrial firms and their owners, tobacco products produced, and tobacco sales locations. The author examines the many causes of the shift in demand for tobacco products over this historical time, as well as the unequal level of tobacco production.The essay discusses the excellent conditions for the growth of tobacco production in the South Caucasus, which eventually became commodities. The report also underlined the Russian government’s interest in spreading this crop, which was the primary raw material for the tobacco sector. The government, which contributed to the region’s colonial exploitation by the Russian and foreign bourgeoisie, benefited financially from the expansion of the cultivation of technological and precious crops.The author finds that the tobacco business in the South Caucasus evolved, improved, and gradually adopted the characteristics of commercial agriculture, which included commodity relations. It is emphasized that the quick expansion of commercial agriculture is closely tied to the emergence of capitalist relationships in agriculture.